Análisis de los créditos agropecuarios de las entidades crediticias calificadas y su incidencia en el desarrollo de las comunidades rurales del cantón Centinela del Cóndor - Villalta Gualán, Eddy Galvanny (2014)
This thesis entitled "Analysis of Agricultural Credit Loan of Qualified Entities and their Impact on the Development of Rural Communities in Canton Sentinel Condor", is based on knowing the importance of credit and its impact on the development of the productive sector, to run the thematic of the research was based on knowing as to increase the efficiency and impact of the credit market in the agricultural and livestock sector in canton Sentinel Condor, of the Province of Zamora Chinchipe, for which a study of economic development, in order to analyze the influence and impact generated in the credit sector, developing the foundations to bring real information on the influence of rural credit in farmers developed. To build the theoretical framework started from a contextualization of the environment to research raising issues as rural financial systems , importance of rural credit , lenders operating in the Sentinel Canton Condor, and also addressed the productive sector to discuss the land tenure and main products generated in this county , allowing better understanding of the study center. For data collection proceeded to implement the planned methodology was to survey 100 farmers in the canton of study, through which it came to determining the entity finance that offer multiple lines of credit and low and comfortable interest to producers is the National Development Bank, which belongs to the same state banks, but due to the complicated procedures that must be performed to access credit, the producers choose to go to private banks, why is the Cooperative CoopMego preferred to request the production credits, and that despite the interest it charges compared to other cooperatives and state-owned banks, this does not require a lot of paperwork, and provides credit in the shortest time possible, so indicate 47% of the respondents. Producers have agreed to these agricultural loans either state or private banks 75% improved production and productivity on their farms by 30% by investing in infrastructure, in areas of greater or lesser livestock, loans also will have allowed better manage their livestock, with the introduction of new techniques and infrastructure, breeding techniques in their cattle herds; these new management techniques has allowed them to expand their scope and provide a value added production that previously only was produced and is now processed, which has caused 69% of respondents have increased their incomes, enabling them to improve the style of life of their families, to provide their children with greater access to education , food, clothing , and improving the quality of their diet. Finally we proceeded to draw the conclusions and recommendations for which was taken as the basis of data obtained in the survey of producers. At this stage of the investigation the results gave birth to a very important conclusion, among the producers who have agreed to credit the citizens and communities Panguintza Zumbi have improved their income and quality of life significantly, not so with the producers of Triumph Natenza Dorado or communities where very few have access to credit, and who have not obtained a loan received technical assistance and performed poorly on their investments. To inform the stakeholders on the results of research through a coordinated effort with the relevant entities as MAGAP, GAD Provincial and Parochial work, some important data are socialized to producers who collaborated with the field study, doubts and disagreements are cleared also indicated the importance they receive technical assistance for the management of their production and their success with productive credit.